2004
DOI: 10.1159/000079690
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes in Patients with Prostate Cancer Managed with Intermittent Androgen Suppression

Abstract: Objectives: To assess the long-term outcomes of patients with prostate cancer managed with intermittent androgen suppression (IAS) following their enrolment in an open, non-randomised feasibility study initiated 10 years ago. Patients and Methods: Patients with prostate cancer who developed marked side effects following androgen deprivation were considered for entry into the study. All patients were required to have been managed with androgen deprivation for a minimum of 9 months and to have achieved PSA remis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Although a number of Phase II studies of intermittent androgen suppression have been undertaken previously, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] the current clinical trial is unique, in that it was designed as a prospective study focusing on a well defined group of patients. The trial spanned an interval of 6 years with a mean followup of 3.7 years and a median follow-up of 4.2 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a number of Phase II studies of intermittent androgen suppression have been undertaken previously, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] the current clinical trial is unique, in that it was designed as a prospective study focusing on a well defined group of patients. The trial spanned an interval of 6 years with a mean followup of 3.7 years and a median follow-up of 4.2 years.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical trial focused on men in biochemical recurrence after they had received radiotherapy for locally advanced prostate cancer and has been used as a guideline for several subsequent large, Phase III, randomized studies. [30][31][32][33][34][35] …”
mentioning
confidence: 99%
“…The practice of cycling between androgen-depleted and androgen-repleted states is not new. Intermittent androgen suppression was introduced initially as a strategy both to delay the outgrowth of castration-resistant cells and to minimize toxicity (8,28). As currently used in an investigational setting, intermittent androgen suppression seeks to maintain a state of medical castration 2 to 3 months beyond the point of maximal PSA decline, at which time ADT is discontinued (29).…”
Section: Discussionmentioning
confidence: 99%
“…Details of the initial management of these patients have been reported previously [11,12]. The first patient recruited began observation of treatment in 1994 after completion of a pilot study, which identified some of the parameters in need of standardisation [13].…”
Section: Methodsmentioning
confidence: 99%